Policing the profession? Regulatory reform, restratification and the emergence of Responsible Officers as a new locus of power in UK medicine. (September 2018) - Bryce, Marie; Luscombe, Kayleigh; Boyd, Alan; Tazzyman, Abigail; Tredinnick-Rowe, John; Walshe, Kieran; Archer, Julian
Abstract: Doctors' work and the changing, contested meanings of medical professionalism have long been a focus for sociological research. Much recent attention has focused on those doctors working at the interface between healthcare management and medical practice, with such 'hybrid' doctor-managers providing valuable analytical material for exploring changes in how medical professionalism is understood. In the United Kingdom, significant structural changes to medical regulation, most notably the introduction of revalidation in 2012, have created a new hybrid group, Responsible Officers (ROs), responsible for making periodic recommendations about the on-going fitness to practise medicine of all other doctors in their organisation. Using qualitative data collected in a 2015 survey with 374 respondents, 63% of ROs in the UK, this paper analyses the RO role. Our findings show ROs to be a distinct emergent group of hybrid professionals and as such demonstrate restructuring within UK medicine. Occupying a position where multiple agendas converge, ROs' work expands professional regulation into the organisational sphere in new ways, as well as creating new lines of continuous accountability between the wider profession and the General Medical Council as medical regulator. Our exploration of ROs' approaches to their work offers new insights into the on-going development of medical professionalism, pointing to the emergence of a distinctly regulatory hybrid professionalism shaped by co-existing professional, managerial and regulatory logics, in an era of strengthened governance and complex policy change. Highlights: Responsible Officers are a new governance elite group in the UK medical profession. They work at the nexus of professional, managerial and regulatory spheres. Differ from other doctor-managers due to accountability for medical performance. Organisational context shapes experiences of this new role. Regulatory reform has engendered a new form of hybrid professionalism.